Dissociable effects of fatigue on performance and metacognition from automatic target cuing in undersea threat detection - Max Kailler Smith; Amelia R. Kracinovich; Brandon J. Schrom; Timothy L. Dunn (Cognitive Research)
Abstract As automation becomes increasingly integrated into complex military tasks, its role in supporting human performance under fatigue warrants careful evaluation. A specific military use case in which automatic target cuing (ATC) is integrated is undersea threat detection (UTD). These types of tasks demand sustained vigilance, accurate classification, and reliable metacognitive judgements. Fatigue, especially due to increased time awake, presents a significant challenge to sustaining high performance. This study investigated whether ATC enhances UTD performance under low fatigue conditions and protects against errors when operators are fatigued, as is common during fleet operations. Thirty-six active-duty service members completed four sessions of a simulated UTD task, with and without an imperfect ATC system, over a ~24-hour wakeful period. Results showed that ATC did not enhance performance when participants were alert, though detection accuracy maintained despite increased fatigue. However, fatigue led to decreased metacognitive sensitivity, reflected in greater confidence for false alarms and reduced trust in the ATC system. These findings suggest that while automation assistance can potentially protect basic task performance under fatigue, it does not prevent the degradation of higher-level cognitive processes, such as metacognitive accuracy and trust in the automation. This study highlights the importance of understanding how automation interacts with cognitive states, especially under fatigue, to optimize its role in critical military operations.